2021
DOI: 10.1111/pan.14328
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and flow in pediatric anesthesia: An educational review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This is likely an example of the often-underestimated difference between pressure and flow, being that changes in CO are not necessarily reflected as a change in blood pressure. 22 Neither ΔVpeak dAo nor ΔVpeak LVOT showed a significant change following volume expansion in both groups. Previous studies using similar methodologies for fluid responsiveness assessment have shown somewhat conflicting data in this regard with both unchanged and even increased ΔVpeak LVOT after fluid loading.…”
Section: Effect Of Volume Expansionmentioning
confidence: 79%
“…This is likely an example of the often-underestimated difference between pressure and flow, being that changes in CO are not necessarily reflected as a change in blood pressure. 22 Neither ΔVpeak dAo nor ΔVpeak LVOT showed a significant change following volume expansion in both groups. Previous studies using similar methodologies for fluid responsiveness assessment have shown somewhat conflicting data in this regard with both unchanged and even increased ΔVpeak LVOT after fluid loading.…”
Section: Effect Of Volume Expansionmentioning
confidence: 79%
“…We read with great interest the review by Karlsson and colleagues that explored the utility (or lack thereof) of using blood pressure as the target metric for titrating care. 1 We wholeheartedly agree with their concerns regarding blood pressure guided titration. They rightly point out that mean blood pressure is the product of cardiac output and systemic vascular resistance.…”
mentioning
confidence: 72%
“…Even if normal blood pressure (macro-circulation) is maintained, adequate end-organ perfusion (micro-circulation) [28] is not guaranteed. It is the flow of oxygenated blood through the tissue capillaries, rather than the systemic pressure, that provides oxygen delivery to the tissues [16 ▪ ].…”
Section: Nectarine – the Lessonsmentioning
confidence: 99%
“…Tissue oxygenation is affected by oxygen extraction and oxygen delivery (cardiac output, oxygenation, hemoglobin concentration). Although arterial oxygenation and hemoglobin are directly measured, cardiac output is approximated from the blood pressure and heart rate measurements but requires a constant systemic vascular resistance [16 ▪ ]. Direct measurements of cardiac output using capnodynamic and electrical cardiometry are being studied as noninvasive methods but are not yet widely available in clinical practice [16 ▪ ].…”
Section: Nectarine – the Lessonsmentioning
confidence: 99%